Thermal and spectroscopic studies of solid oxamate of light trivalent lanthanides - Caires, F. J. [UNESP]; Lima, L. S. [UNESP]; Gomes, D. J C [UNESP]; Gigante, A. C. [UNESP]; Treu-Filho, O. [UNESP]; Ionashiro, Massao [UNESP] (Springer Nature, 2013)
Solid-state LnL3·1.25H2O compounds, where L is oxamate and Ln is light trivalent lanthanides, have been synthesized. Simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), experimental and theoretical infrared spectroscopy, TG-DSC coupled to FTIR, elemental analysis, complexometry, and X-ray powder diffractometry were used to characterize and to study the thermal behavior of these compounds. The results led to information about the composition, dehydration, thermal stability, thermal decomposition, and gaseous products evolved during the thermal decomposition of these compounds in dynamic air atmosphere. The dehydration occurs in a single step and through a slow process. The thermal decomposition of the anhydrous compounds occur in a single (Ce), two (Pr), and three (La, Nd to Gd) steps with the formation of the respective oxides, CeO2, Pr 6O11, and Ln2O3 (Ln = La, Nd to Gd). The theoretical and experimental spectroscopic study suggests that the carboxylate group and amide carbonyl group of oxamate are coordinate to the metals in a bidentate chelating mode. © 2012 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Light trivalent lanthanides; Oxamate; Theoretical calculations; Thermal behavior; Anhydrous compounds; Carbonyl groups; Carboxylate groups; Complexometry; Dynamic air atmosphere; FTIR; Gaseous products; Single-step; Spectroscopic studies; Thermal behaviors; Trivalent lanthanides; X-ray powder diffractometry; Amides; Carboxylation; Decomposition; Dehydration; Differential scanning calorimetry; Gadolinium; Infrared spectroscopy; Neodymium; Thermogravimetric analysis; Spectroscopic analysis